Numerical calculation of fractional derivatives of non-smooth data - Tenreiro Machado, J. A. (2019)
This paper addresses the calculation of fractional derivatives of fractional order for non-smooth data. The noise is avoided by adopting an optimization formulation using genetic algorithms (GA). Given the flexibility of the evolutionary schemes it is established a hierarchical GA composed by a series of two GAs, each one with having a distinct fitness function.